Design of Electrical Stimulation Waveform for Enhancing Saltiness and Experiment on Low-Sodium Dieters - Kaji, Yoshinobu; Sato, Ai; Miyashita, Homei (Frontiers in Virtual Reality, 2022)
Electric tastes can present various taste modulation effects using stimulation waveforms. Presenting and stopping cathodal stimulation or presenting anodal stimulation, for example, can enhance the saltiness of foods and drinks. If the taste of low-sodium foods improves because of these effects, it can provide low-sodium dieters with both mental satisfaction and nutritional health benefits. However, no studies on the effect of saltiness enhancement on electric taste in low-sodium dieters have been conducted. In this study, we first designed and investigated a stimulation waveform suitable for saltiness enhancement of low-sodium foods. This stimulation waveform combined the effects of presenting and stopping cathodal stimulation and presenting anodal stimulation and showed a saltier enhancement than the existing waveforms. Next, we conducted an experiment with individuals who were or had been on a low-sodium diet. In this experiment, the effect of saltiness enhancement on the proposed stimulation waveform was investigated using saltwater gel samples with the same saltiness as low-sodium and ordinary foods. The results suggest that presenting the proposed stimulation waveform when eating foods with a 30% reduction in salt content can present a saltiness equivalent to that of ordinary foods. Furthermore, the discomfort caused by electrical stimulation was not severe enough to be a problem for most participants. Finally, assuming the use of electric tastes in daily life, this study attempted to qualitatively analyze the changes in saltiness intensity and flavor of low-sodium miso soup.